2006
DOI: 10.1128/aem.00803-06
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of a Non-Male-Killing Spiroplasma in Natural Populations of Drosophila hydei

Abstract: Male-killing phenotypes are found in a variety of insects and are often associated with maternally inherited endosymbiotic bacteria. In several species of Drosophila, male-killing endosymbionts of the genus Spiroplasma have been found at low frequencies (0.1 to 3%). In this study, spiroplasma infection without causing malekilling was shown to be prevalent (23 to 66%) in Japanese populations of Drosophila hydei. Molecular phylogenetic analyses showed that D. hydei was infected with a single strain of spiroplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 47 publications
9
66
0
Order By: Relevance
“…Although the nuclear factors of Sevelen and Hikone suppressed the expression of male killing to considerable levels, they could not accomplish complete suppression of male killing (that is, when mothers become sufficiently old, suppression of male killing is attenuated and eventually lost). Similar results were obtained in an earlier study using the spiroplasma strain WSRO (male-killing spiroplasma derived from D. willistoni), which is closely related to NSRO (Montenegro et al, 2005;Kageyama et al, 2006). Specifically, microinjection of WSRO-laden hemolymph into D. melanogaster revealed that the male-killing intensity was high in Oregon-R, but weak in Sevelen (Sakaguchi and Poulson, 1963).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although the nuclear factors of Sevelen and Hikone suppressed the expression of male killing to considerable levels, they could not accomplish complete suppression of male killing (that is, when mothers become sufficiently old, suppression of male killing is attenuated and eventually lost). Similar results were obtained in an earlier study using the spiroplasma strain WSRO (male-killing spiroplasma derived from D. willistoni), which is closely related to NSRO (Montenegro et al, 2005;Kageyama et al, 2006). Specifically, microinjection of WSRO-laden hemolymph into D. melanogaster revealed that the male-killing intensity was high in Oregon-R, but weak in Sevelen (Sakaguchi and Poulson, 1963).…”
Section: Discussionsupporting
confidence: 74%
“…For artificial infection of NSRO, microinjection of NSROladen hemolymph was performed as described earlier (Kageyama et al, 2006). Briefly, collection and injection of hemolymph was conducted under a dissecting microscope with thin glass capillary tubes made with a microelectrode puller (PN-3; Narishige, Tokyo, Japan).…”
Section: Transfection Of Nsromentioning
confidence: 99%
“…The observed spiroplasma is a close relative to MK spiroplasmas from other Drosophila species and, at the same time, the most basal taxon of the clade. Two parsimonious scenarios for the evolution of MK in this spiroplasma clade were suggested [17]. First, a common non-MK ancestor of the clade could evolve MK ability, which was subsequently lost in the spiroplasma lineage of D. hydei, a scenario indicative of the evolutionary branching we observed in our study.…”
Section: Discussionmentioning
confidence: 66%
“…However, highly efficient male-killers might have evolved gradually from less-efficient male-killers, and from bacteria that did not possess any MK ability [17]. Our analysis reveals that less efficient male-killers are not viable where highly efficient male-killers can persist (electronic supplementary material, appendix S3).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation